Preparation of basalt fibers grafted with amine terminated urea-based oligomer and its application in reinforcing conventional glass ionomer cement. (November 2021) - Bao, Xiaozhen; Liu, Fang; He, Jingwei
Abstract: The purpose of this study was to improve interfacial interaction between basalt fibers (BF) and glass ionomer cement (GIC) matrix with grafting amine terminated urea-based oligomer (DIEDA) onto the surface of BF. The DIEDA-BF was prepared by the reaction between 3-aminopropyl- triethoxysilane (APS) modified BF with Isophorone diisocyanate (IPDI) and followed with ethylenediamine (EDA). The reaction was repeated to obtain three generations of DIEDA-BF which were marked as DIEDA-BF-G1, DIEDA-BF-G2, and DIEDA-BF-G3, respectively. X-ray photoelectron spectroscopy (XPS) was used to characterize DIEDA-BF. 3D morphology analysis was taken to investigate the variation of BF after being treated with EDA. Three-point bending-test, compressive strength (CS) test, and fracture toughness (FT) were used to evaluate the reinforcement effect of DIEDA-BF on commercial GIC (GC Fuji IX). Water sorption (WS) and solubility (SL) were measured according to the mass variation at fixed time intervals. The changes of flexural strength (FS) and modulus (FM) after water immersion were used to evaluate the water-aging resistance of DIEDA-BF reinforced GIC. Pure GIC and APS reinforced GIC (APS-GIC) were used as double control groups. The XPS analysis indicated that DIEDA was successfully grafted onto the surface of BF. 3D morphology analysis revealed that BF could be corroded in EDA, thus DIEDA-BF-G3 had lower N content on the surface than DIEDA-BF-G2 . The results of mechanical tests showed that DIEDA-BF-G1 and DIEDA-BF-G2 had the best reinforcement effect. The DIEDA-BF-G1 reinforcement GIC (DIEDA-BF-G1 -GIC) was chosen for WS, SL, and water aging resistance test further. The results showed that all fiber reinforced GICs had higher WS than pure GIC, and the relationship in SL between fiber reinforced GICs and pure GIC varied with immersion time. The FS of DIEDA-BF-G1 -GIC decreased after one week of water immersion, and had no variation after prolonging the immersion time. After three months of water immersion, DIEDA-BF-G1 -GIC still had much higher FS than pure GIC and APS-BF-GIC. DIEDA could improve the interfacial interaction between BF and GIC matrix. After long term of water immersion, DIEDA-BF reinforced GIC still had FS higher than 50 MPa, which even met the ISO requirement in FS for dental resin composite. Therefore, GIC/DIEDA modified BF composite had potential to be used in stress bearing areas in dentistry.